Comparative advantage, demand for external finance, and financial development - Đỗ-Quý-Toàn (Policy research working paper, 2006)
"The differences in the levels of financial development between industrial and developing countries are large and persistent. Theoretical and empirical literature has argued that these differences are the source of comparative advantage and could therefore shape trade patterns. This paper points out the reverse link: financial development is influenced by comparative advantage. The authors illustrate this idea using a model in which a country's financial development is an equilibrium outcome of the economy's productive structure: financial systems are more developed in countries with large financially intensive sectors. After trade opening demand for external finance, and therefore financial development, are higher in a country that specializes in financially intensive goods. By contrast, financial development is lower in countries that primarily export goods which do not rely on external finance. The authors demonstrate this effect empirically using data on financial development and export patterns in a panel of 96 countries over the period 1970-99. Using trade data, they construct a summary measure of a country's external finance need of exports and relate it to the level of financial development. In order to overcome the simultaneity problem, they adopt a strategy in the spirit of Frankel and Romer (1999). The authors exploit sector-level bilateral trade data to construct, for each country and time period, a predicted value of external finance need of exports based on the estimated effect of geography variables on trade volumes across sectors. Their results indicate that financial development is an equilibrium outcome that depends strongly on a country's trade pattern. "--World Bank web site